Knowledge and Utilization of Antenatal and Postnatal Services in an Urban area of South-East Delhi: A Cross-Sectional Study - Sehla Tabassum; Shyambhavee Behera; Kartikey Yadav; Korbilli Gautami (Healthline)
Introduction: Poorer pregnancy outcomes are linked to inadequate antenatal care (ANC) and Postnatal care (PNC). Thus, adequate knowledge and utilization of these services among expectant mothers becomes the key to achieving healthy pregnancy outcomes. Objective: To assess the knowledge and utilization of ANC and PNC services among women who delivered in last 1 year residing in an Urban area of South-East Delhi. Methods: This was a cross-sectional study conducted among 150 women who delivered within the last one year residing in an urban area of South-East Delhi. Data collection between May 2024 to July 2024 was done with the help of pre-designed, validated, structured questionnaire using simple random sampling. Statistical analysis was done using SPSS which included computation of proportions and univariate analysis, which was done using chi-square test. Result: Good knowledge regarding basic ANC, Janani Suraksha yojana (JSY) and Pradhan Mantri Matru Vandana Yojana (PMMVY), Janani Shishu Suraksha Karyakram (JSSK), Anganwadi services and Home-based Newborn Care (HBNC) was reported by 140 (93.3%), 55 (36.7%), 127 (84.7%), 104 (69.3%), and 113 (75.3%) of the study participants, respectively. Good utilization of the services including basic ANC, JSSY and PMMVY, JSSK, Anganwadi services and HBNC was reported by 139 (92.7%), 13 (8.7%), 94 (62.7%), 104 (55.3%), and 113 (75.3%) of the study participants, respectively. Conclusion: The study reported good knowledge and utilization of basic ANC services. However, significant gaps were reported for the services provided under JSY, PMMY followed by JSSK, Anganwadi services and HBNC.